Application of Sharia Economic Principles in Stock Trading - Yana Mas’ud Tasdiq; Sugeng Ahmad Riyadi; Nurul Lailatul Vitriyah; Atika Rahma; Wiwin Suhada (Lafadz Jaya Publisher, 2026)
Stock trading is a key asset in the investment world, but its practice is often influenced by non-sharia economic aspects that do not always align with Islamic principles. Therefore, this study aims to analyze the application of sharia economic principles in stock trading on the Indonesian stock exchange. This study aims to describe the application of sharia economic principles in stock trading in the Indonesian capital market. This study uses a descriptive qualitative approach by conducting in-depth interviews with investors, market analysts, and sharia finance practitioners. Data were collected through interviews and processed through thematic analysis to identify themes and subthemes related to the application of sharia economic principles in stock trading. The results show that most companies implementing sharia economic principles in their stock trading have increased transparency and accountability in reporting financial performance and business policies. They have also improved the quality of management and internal auditing to ensure that all transactions and business decisions are in accordance with sharia principles. However, this study also found that there are still many challenges faced by companies in implementing sharia economic principles in stock trading, such as the lack of ability and knowledge of sharia principles among company staff and the lack of clear and consistent regulations from capital market authorities.